Effectiveness of Group Guidance Services Using Socio-drama Techniques to Reduce Acts of Discrimination in High School Students - Kharismaylinda, Joya; Harahap, Ade Chita Putri (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the effectiveness of group guidance services with sociodrama techniques to reduce acts of discrimination in Al-Washliyah 22 Medan high school students. The research approach is Quantitative, with the type of research using Quasi Experimental Design with treatment in the form of sociodrama conducted six times a meeting. The population of the study was the X-grade students of SMA Al-Washliyah 22 Medan totaling 2 study groups consisting of X MIA majors, Class A 32 Students and Class B 32 Students. Sampling was done by purposive sampling technique consisting of Class A 8 students and Class B 7 students. Techniques used in data collection using Experiments are conducted under controlled conditions and often involve a control group. The data analysis method used is paired sample t-test to test the hypothesis of the average of two samples and to find out if there is a difference before and after the treatment is carried out. In the paired sample t-test test, if the sig. two-tailed value is 0.05> the sig. 2-tailed value means there is a difference, and if the sig. two-tailed value> 0.05 means there is no difference. 2-tailed value of 0.000 < 0.05 in the experimental class, and 0.031 > 0.05 in the control class, which means that there is a difference in the average decrease in student discrimination in the experimental class. It can be concluded that group guidance services with sociodrama techniques are effective in reducing discrimination in high school students.